#### Answer

Even

#### Work Step by Step

$f(-x)=\frac{(-x)^{2}}{(-x)^{4}+1}=\frac{x^{2}}{x^{4}+1}=f(x)$
$\therefore f(x)$ is even

Published by
Cengage Learning

ISBN 10:
1285741552

ISBN 13:
978-1-28574-155-0

Even

$f(-x)=\frac{(-x)^{2}}{(-x)^{4}+1}=\frac{x^{2}}{x^{4}+1}=f(x)$
$\therefore f(x)$ is even

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.